2020
DOI: 10.1101/2020.08.28.271759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Micro-engineered Human Colon Intestine-Chip Platform to Study Leaky Barrier

Abstract: The intestinal epithelial barrier supports the symbiotic relationship between the microbiota colonizing the intestinal epithelium and the host immune system to maintain homeostasis. Leaky barrier is increasingly recognized as part of the pathogenesis of a number of chronic conditions in addition to inflammatory and infectious diseases. As our understanding on the regulation of the barrier remains limited, effective therapeutic targeting for the compromised barrier is still an unmet need. Here we combined advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…To establish Colon Intestine-Chips, colonic organoids were seeded on S-1 chips (Emulate Inc., Boston, MA, USA) and processed as follows [36](Apostolou et al, unpublished): Chips were washed with 70% ethanol, cell culture water, and ER2 reagent (Emulate Inc.), and then activated with ER1 (Emulate Inc.) working solution (0.5 mg/mL ER1 powder in ER2 solution) using 20 min UV light treatment (Nailstar, NS-01 EU/UK). The chips were, then, washed with ER2 and PBS and the inner surfaces of both channels and the porous PDMS membrane coated with extracellular matrix proteins (ECM).…”
Section: Colon Intestine-chipsmentioning
confidence: 99%
“…To establish Colon Intestine-Chips, colonic organoids were seeded on S-1 chips (Emulate Inc., Boston, MA, USA) and processed as follows [36](Apostolou et al, unpublished): Chips were washed with 70% ethanol, cell culture water, and ER2 reagent (Emulate Inc.), and then activated with ER1 (Emulate Inc.) working solution (0.5 mg/mL ER1 powder in ER2 solution) using 20 min UV light treatment (Nailstar, NS-01 EU/UK). The chips were, then, washed with ER2 and PBS and the inner surfaces of both channels and the porous PDMS membrane coated with extracellular matrix proteins (ECM).…”
Section: Colon Intestine-chipsmentioning
confidence: 99%
“…S6 and S7A), where they form a tight, polarized barrier, containing the full range of mature intestinal cell types. We have previously shown that the inclusion of luminal flow, peristaltic motion, and an endothelial layer enhances the maturation and physiological fidelity of the barrier, compared with organoids in conventional 3D culture(35).…”
Section: Resultsmentioning
confidence: 99%
“…Different models of gastrointestinal organs and organoids-on-a-chip have been innovatively explored in drug testing, some of which are already GOoC models, summarized in table 1 [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Small Intestineorganoid-on-achipmentioning
confidence: 99%
“…In the gastrointestinal system, it comprises a range of diseases, from the less defined irritable bowel syndrome to full impairment of intestinal function in inflammatory bowel disease (IBD) [60]. A leaky barrier is gradually being appointed as part of these inflammatory and infectious diseases [42]. Apostolou et al [42] used the proprietary Human Emulation System Organ-on-a-chip by Emulate® to develop their system: Colon Intestine-Chip.…”
Section: Inflammation Modelsmentioning
confidence: 99%